1993
DOI: 10.1172/jci116361
|View full text |Cite
|
Sign up to set email alerts
|

Direct interactions of human lymphocytes with the yeast-like organism, Cryptococcus neoformans.

Abstract: Lymphocytes, especially CD4+ T cells, are essential for clearance of the yeast-like organism Cryptococcus neoformans from the infected host. The mechanism(s) by which the lymphocytes facilitate elimination of cryptococci has not been elucidated. It is generally thought, however, that lymphocytes reactive with C. neoformans indirectly function by production of lymphokines to enhance clearance of the organism by natural effector cells such as macrophages. In the present study, we assessed the ability of freshly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 42 publications
4
74
0
Order By: Relevance
“…When the YT cells were separated from the C. neoformans, YT cells completely lost their anticryptococcal activity, suggesting that the YT cell-mediated antifungal activity is not due to soluble factors, but rather, it is contact dependent. This is consistent with previous studies that observed direct contact between human T cells, human NK cells, or mouse NK cells with C. neoformans by microscopic techniques (45)(46)(47)(48)(49). The importance of cell contact and the magnitude of the anticryptococcal activity are further emphasized by the observation that the growth of C. neoformans increased as the number of YT cells was increased on the other side of the membrane.…”
Section: Discussionsupporting
confidence: 91%
“…When the YT cells were separated from the C. neoformans, YT cells completely lost their anticryptococcal activity, suggesting that the YT cell-mediated antifungal activity is not due to soluble factors, but rather, it is contact dependent. This is consistent with previous studies that observed direct contact between human T cells, human NK cells, or mouse NK cells with C. neoformans by microscopic techniques (45)(46)(47)(48)(49). The importance of cell contact and the magnitude of the anticryptococcal activity are further emphasized by the observation that the growth of C. neoformans increased as the number of YT cells was increased on the other side of the membrane.…”
Section: Discussionsupporting
confidence: 91%
“…This is supported by the observation that perforin acts as a gateway for granzymes through the plasma membrane. Both of these events might require intimate contact of the T lymphocyte and the target, and previous studies have shown that intimate contact between the T lymphocytes and C. neoformans is required for the anticryptococcal activities (23,46,67). Thus, it may be that perforin is required for granulysin to access the compartment containing mycobacteria, but granulysin is directly active on extracellular C. neoformans at the conjugation region.…”
Section: Discussionmentioning
confidence: 99%
“…However, C. neoformans is a fungal pathogen that primarily afflicts immunocompromised subjects such as those affected by HIV, where the cellmediated immune response (T and NK) is significantly impaired. In these patients, phagocytosis might not represent an effective mechanism of defense by the host, when the activation of T and/or NK cells and, thus, the production of activated macrophages are significantly reduced (6,(47)(48)(49). Moreover, in the case of facultative intracellular pathogens, such as C. neoformans, for which intracellular growth can be a favorable condition, phagocytosis may represent a successful strategy for better survival in the host.…”
Section: Discussionmentioning
confidence: 99%